Comparing the Effectiveness of Emotion-Focused Therapy and Transactional Analysis Therapy on Interpersonal Problems in Conflicted Women Seeking Divorce - Amrollahi Biuki , Atefeh; Lashgari, Mahdi; Aghaei, Hakime (Psychology of Woman Journal, 2026)
Objective: The present study aimed to compare the effectiveness of emotion-focused therapy and transactional analysis therapy on reducing interpersonal problems in conflicted women seeking divorce.Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest format including a control group and a three-month follow-up period. The statistical population consisted of conflicted women seeking divorce who were referred to counseling and psychological service centers in Tehran. Using purposive sampling and based on inclusion and exclusion criteria, 45 participants were selected and randomly assigned into three groups: emotion-focused therapy, transactional analysis therapy, and control (15 participants in each group). The experimental groups received eight sessions of intervention, while the control group remained on a waiting list. Data were collected using the Interpersonal Problems Questionnaire. Statistical analyses were conducted using SPSS-26 at both descriptive and inferential levels, including multivariate analysis of covariance (MANCOVA), repeated measures analysis of variance, and Bonferroni post hoc tests.Findings: The results of analysis of covariance indicated that both emotion-focused therapy (F = 25.91, p < 0.001, η² = 0.558) and transactional analysis therapy (F = 39.62, p < 0.001, η² = 0.595) had significant effects on reducing interpersonal problems compared to the control group. Repeated measures analysis revealed a significant effect of time (F = 32.53, p < 0.001, η² = 0.437) and a significant interaction between time and group (F = 16.07, p < 0.001, η² = 0.433), indicating sustained changes over time. Bonferroni post hoc tests showed that both experimental groups significantly differed from the control group (p < 0.001), while no significant difference was found between the two interventions (p = 0.452).Conclusion: Both emotion-focused therapy and transactional analysis therapy were effective in reducing interpersonal problems in conflicted women seeking divorce, and their effects were stable over time, with no significant difference in effectiveness between the two approaches.